Potencial antitumoral e toxicidade do (E)-1’-((4-bromo-benzilideno)amino)5’- oxo-1’5’-dihidro-10H-espiro[acridina-9,2’-pirrol]-4’-carbonitrila (AMTAC-19), um novo derivado espiro-acridínico - Sousa, Valgrícia Matias de (2020)
Cancer is a term used to define a group of diseases characterized by the uncontrolled proliferation of transformed cells, resulting from the progressive accumulation of genetic and epigenetic changes. Several problems in cancer therapy, such as the development of resistance to treatment and high toxicity, drive the search for new drugs. In this context, acridine compounds that have reports of antitumor activity, mainly associated with DNA intercalation and inhibition of topoisomerases, stand out. The objective of this work was to evaluate the cytotoxicity of spiro-acridine derivatives in tumor and non-tumor cells, as well as the possible mechanisms of action of the most promising compound, in the most sensitive tumor line. The cytotoxicity of the compounds was evaluated by the MTT reduction assay in tumor cell lines (HCT-116, MCF-7, HeLa, PC-3 and SK-MEL-28) and non-tumor cells (HaCat and L929), as well as in peripheral blood mononuclear cells (PBMC). 5'-oxo-1 '- ((4- (piperidine-1-yl) benzylidene) amino) -1', 5'-dihydro-10H-spiro [acridine-9,2'-pyrrole] -4'- carbonitrile (AMTAC-23) induced the lowest percentage of growth inhibition in PC-3 tumor cells (0 ± 0.85%), and in non-tumoral L929 cells (11.93 ± 1.91%). The most cytotoxic compound was (E) -1 '- ((4-bromo-benzylidene) amino) 5'-oxo-1'5'-dihydro-10H-spiro [acridine-9,2'-pyrrole] -4 '-carbonitrile (AMTAC-19), which inhibited the growth of HCT116 colorectal carcinoma cells by 88.56 ± 0.58%, and of non-tumoral L929 cells by 70.42 ± 1.74%. The concentration that inhibits 50% of cell growth (CI50) was 10.35 ± 1.66 µM in HCT-116 cells, and 4.89 ± 1.18 µM in PBMC, after 72 hours of treatment with AMTAC-19. The analysis of the selectivity index showed that this acridine has a more selective effect on HCT-116 cells, when compared to the standard drug doxorubicin. Then, the effects of AMTAC-19 on the cell cycle, the induction of apoptosis and the production of reactive oxygen species (ROSs), in concentrations of 10 or 20 µM, were evaluated after 48 hours of treatment. AMTAC-19 induced a significant increase in the sub-G1 peak (p <0.05), which is associated with apoptosis, as well as stopping in phases S and G2 / M (p <0.05), preventing the synthesis of genetic material and cell multiplication. An increase in staining with annexin V and propidium iodide (p <0.05) was observed, which is indicative of cell death due to apoptosis. Characteristic morphological changes of apoptosis were observed after treatment with AMTAC-19 by means of laser confocal microscopy analysis using acridine orange and propidium iodide. Such changes included the presence of membrane blebs, DNA fragmentation and chromatin condensation, which confirms the presence of apoptotic cells. In addition, AMTAC-19 reduced the production of reactive oxygen species (p <0.05) in HCT-116 cells, which suggests that the antioxidant effect is part of the compound's anti-tumor mechanism of action. The data presented indicate that AMTAC-19 induces antitumor activity in HCT-116 cells by interfering with the progression of the cell cycle and inducing apoptosis and antioxidant effect.